Engaging contradictions : theory, politics, and methods of activist scholarship - Hale, Charles R., 1957- (Global, area, and international archive., 2008)
"Scholars in many fields increasingly find themselves caught between the academy, with its demands for rigor and objectivity, and direct engagement in social activism. Some advocate on behalf of the communities they study; others incorporate the knowledge and leadership of their informants directly into the process of knowledge production. What ethical, political, and practical tensions arise in the course of such work? In this wide-ranging and multidisciplinary volume, leading scholar-activists map the terrain on which political engagement and academic rigor meet."--Book cover.